The Office as a Mixing Pot and Playground. An Ethnographic Study at a Creative Workplace - Serrano-Martínez, Cecilia (Qualitative Sociology Review, 2016)
This paper aims to contribute to knowledge of the factors which inform the grouping of creative workers in particular places. It is based on a case study of Aragón, a region of Spain, and draws on a period of nine months of ethnographic work among a particular group of creative workers. The main hypothesis is that there are visual components in the work environment that are stimulating for workers and there is a number of creative flows in these workspaces. I have selected one office that is occupied by two different groups of creative professionals: web designers and programmers. The research concludes that there is evidence that a shared set of cultural values, ideas about work organization, and a hybrid work-life balance are significant to the location choices of creative workers. The research is relevant as a contribution to knowledge about how creative places work.